Do fomento à inovação às flexibilidades TRIPs: soluções viáveis para o problema da indisponibilidade de medicamentos de combate às doenças negligenciadas - Lucas Bernardes Araujo (2014)
This study aims the analysis of the problem related to the access to medicines for the treatment of diseases considered neglected. The characterization of some diseases as "neglected" is due to the low interest of private institutions to invest in R&D (Research and Development) to obtain innovative therapeutic solutions in these areas. The lack of interest is justified by the low expectations of financial return for these investments, since the diseases primarily affect poor people. The research supported the hypothesis that it is possible to expand access to these drugs, either by the use of mechanisms to flexible the patents of drugs available in the market, as by the government incentive for research and development of innovative drugs. To verify the hypothesis, international and domestic laws governing intellectual property, as well as the relevant bibliographic production were analyzed. Considering the finding of flexibility mechanisms of the patent law, decisions from the dispute settlement body of the World Trade Organization (WTO) and the suitability of these mechanisms in Brazil were evaluated. Similarly, we investigated methods proposed by researchers to encourage innovation in the area and its conformation to the Brazilian reality. The work had, as its theoretical basis, the fact that the current patent system is unable to solve the serious problem of unavailability of drugs for neglected diseases. In conclusion, the hypothesis was confirmed, in the sense that there are important mechanisms available to the public administrator, compatible with the Brazilian legal and financial realities and able to narrow the access of the poor to innovative therapeutic solutions.